The effect of strategy training in the comprehension of academic reading materials - Azuro Umairah Mohd Rozin (2010)
Reading skills play an important role in mastering a language and knowledge. Therefore it is important to expose students to practice strategic reading habits since it will assist them to perform in academic journey. The current investigation aims to observe the effect of reading strategies training towards subjects reading comprehension performance as well as the subjects level of awareness utilizing reading strategies when they perform their reading tasks. The subjects in this investigation were 30 first semester students from the Commerce Department of Sultan Azlan Shah Polytechnic. 15 subjects were Diploma of Marketing (DPR) students and another 15 subjects were Diploma of Accountancy (DAT) students. DPR students were assigned to the experimental group meanwhile DAT students were assigned to the control group. The experimental group undergone 60 minute reading strategy training for 12 weeks meanwhile the control group did not receive any training. In order to observe the effect of the training, pre-test and post-test for reading comprehension test and survey on reading strategies (SORS) were administered to the experimental group. The pre-test and post-test were also conducted to the control group so that the performance for both group could be compared. The data obtained from the tests were analyzed via SPSS. The t-test conducted had revealed that the experimental group showed a significant improvement in reading comprehension test score and survey on reading strategy score. This evidence has proven that the reading strategy training exposed to the experimental group managed to facilitate the subjects to read and further perform better in comprehending the reading text.